MASIHKAH BERTAHAN? STRATEGI COPING STRES TENAGA KESEHATAN DI MASA PANDEMI COVID-19 - Wilhelmina Asterix Nicolas; Doddy Hendro Wibowo (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Stress is a change in a person's emotions and behavior that is influenced by various factors. During the Covid-19 pandemic, the prevalence of stress in health workers is increasing due to their duty as the front line to deal with the coronavirus. Stress can be overcome with coping strategies to minimize the adverse effects that can affect daily activities. This study aims to identify coping strategies used by health workers while working during the Covid-19 pandemic. This study uses a qualitative approach with data collection methods of observation and interviews. The sample was taken using purposive sampling as many as three health workers with the research sample criteria, namely, health workers at the Batheramas Hospital aged 35-50 years, working experience of more than 5 years and tasked with handling positive patients with the corona virus during the Covid-19 pandemic. Data were analyzed using an interactive model developed by Miles and Huberman. The results showed that the use of emotion focused coping-accepting responsibility was the most frequently used form of coping by the three subjects.